Corrigendum: The significance of cephalopod beaks as a research tool: An update - Xavier, José C; Golikov, Alexey V; Queirós, José P; Perales-Raya, Catalina; Rosas-Luis, Rigoberto; Abreu, José; Bello, Giambattista; Bustamante, Paco; Capaz, Juan C; Dimkovikj, Valerie H; González, Ángel F; Guímaro, Hugo; et al. (Frontiers in Physiology, 2023)
[This corrects the article DOI: 10.3389/fphys.2022.1038064.].